Proposal for a Flipped Classroom Strategy for Teaching Academic Writing at the University Level - Ramos-Rivas, Karla (2025)
Writing in the academic environment is not only practicing the skills, strategies or resources acquired in secondary education. Contrary to what students believe, writing at university requires mastering this competence in order to access social practices located in the specific disciplinary field, in which it will be necessary to master the construction of rhetorical, syntactic and discursive structures. The teaching of academic writing becomes the ideal content to be approached by means of didactic strategies of practical modality such as the inverted classroom. Much of the failure in the teaching of writing lies in the fact that it has not been treated as a procedural content that requires abundant practice and the conscious analysis of errors, since students face a complex socio-cognitive process. Thus, this article offers a proposal of a didactic strategy of inverted classroom for the teaching and evaluation of academic writing at the university level, which was used during the second semester of 2023 at the University of Costa Rica.